2021
DOI: 10.1155/2021/8111436
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Effect of Freeze‐Thaw Cycles on Axial Tension and Compression Performance of Concrete after Complete Carbonization

Abstract: The effect of freeze-thaw cycles on the axial tension and axial compression properties of completely carbonized concrete are investigated in this study. Three grade concrete specimens (C30, C40, and C45) were fabricated. The freeze-thaw cycle test was carried out on the completely carbonized specimens, followed by axial tension and axial compression tests. The results show that completed carbonization increases the axial tensile peak stress of C30, C40, and C45 concrete specimens by 8.7%, 9.7%, and, 12.1%, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…It mainly focuses on the causes of cracks, crack control and numerical simulation, characteristics of cracks, and so on [10][11][12][13]. However, there are relatively few experimental studies on the carbonation law of concrete at the crack [14][15][16][17]. Miao et al [18] found that micro cracks and micropores in concrete were important factors affecting the The goal of this research is to decipher the carbonation law of cracked cement paste and to investigate the carbonation mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…It mainly focuses on the causes of cracks, crack control and numerical simulation, characteristics of cracks, and so on [10][11][12][13]. However, there are relatively few experimental studies on the carbonation law of concrete at the crack [14][15][16][17]. Miao et al [18] found that micro cracks and micropores in concrete were important factors affecting the The goal of this research is to decipher the carbonation law of cracked cement paste and to investigate the carbonation mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the road construction in the seasonal freezing area of northwest China, the concrete structures not only have to withstand the deterioration caused by freezing and thawing, but also inevitably sufer the isodynamic load caused by construction blasting disturbance [1][2][3]. In this complex environment, the internal cracks in concrete are intensifed and expanded, and the degree of damage is aggravated, which is macroscopically manifested as a decrease in the mechanical properties of concrete [4,5], seriously afecting the durability of the use of the structure and posing a potential threat to the development of the subsequent performance of the concrete structure and its service life [6,7]. Terefore, it is of great signifcance to investigate the dynamic mechanical properties and damage change characteristics of concrete under freeze-thaw cycle conditions to predict the performance deterioration law of concrete under freeze-thaw and dynamic load disturbance.…”
Section: Introductionmentioning
confidence: 99%